2013
DOI: 10.1016/j.jmii.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors for oropharyngeal colonization of yeasts in human immunodeficiency virus-infected patients: A prospective cross-sectional study

Abstract: Despite previous studies showing that protease inhibitors decreased Candida adhesion to epithelial cells in vitro, the current study found protease inhibitor-containing antiretroviral therapy predisposed to oropharyngeal yeast colonization in HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…Katiraee et al (2010a,b) and Badiee et al (2010) reported incidence of oral candidiasis of 59Á0 and 71Á5%, respectively, in Iranian HIVinfected patients. Similar prevalence rates of oral candidiasis were reported in different countries, for example, in Taiwan 51Á4%, Lebanon 76Á0%, Cameroon 73Á0% and South Africa 60Á0% (Lin et al 2013;dos Santos Abrantes et al 2014;Berberi et al 2015). In addition, Katiraee et al (2010a,b) revealed that the most common symptoms of oral candidiasis in HIV-positive patients were thrush (38Á0%) and perleche (20Á0%).…”
Section: Population Studysupporting
confidence: 72%
See 3 more Smart Citations
“…Katiraee et al (2010a,b) and Badiee et al (2010) reported incidence of oral candidiasis of 59Á0 and 71Á5%, respectively, in Iranian HIVinfected patients. Similar prevalence rates of oral candidiasis were reported in different countries, for example, in Taiwan 51Á4%, Lebanon 76Á0%, Cameroon 73Á0% and South Africa 60Á0% (Lin et al 2013;dos Santos Abrantes et al 2014;Berberi et al 2015). In addition, Katiraee et al (2010a,b) revealed that the most common symptoms of oral candidiasis in HIV-positive patients were thrush (38Á0%) and perleche (20Á0%).…”
Section: Population Studysupporting
confidence: 72%
“…Similar prevalence rates of oral candidiasis were reported in different countries, for example, in Taiwan 51·4%, Lebanon 76·0%, Cameroon 73·0% and South Africa 60·0% (Lin et al . ; dos Santos Abrantes et al . ; Berberi et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rates of non‐ albicans Candida spp. continue to rise to approximately 30% in many cohorts, influenced by geographical location and resource setting . Recent US data suggest that C. albicans is responsible for 62–68% of oropharyngeal Candida spp.…”
Section: Epidemiology Of Candidiasismentioning
confidence: 99%